ANALISIS KEGAGALAN COOLER MOTOR POMPA CIRCULATING WATER PUMP DI PLTU (Studi Kasus Di PLTU) - Dian Susanto; Muki Satya Permana; Rochim Suratman (PROCEEDING STIMA)
Pump CWP (Circulating Water Pump) serve to provide water for the condenser is also for the makeup water tank. CWP structure consists of a suction bell, impeller chamber and impeller, diffuser, discharge elbow, lower the main shaft and the main upper shaft, electric motor. Cooler motors wrapped around the walls of the pump motor CWP. Cooler tube has a diameter of 14 mm and a thickness of 1 mm. In November 2011 there has been damage to the engine water pump. Date March 15, 2013 experienced the same case, the damage occurred in the pump cooler pump motor CWP bottom (lower shaft CWP 6). Cooler winding temperature at around 35-75 o C. This section serves to cool the temperature of the pump motor. Cooler pump motor is made of copper-type C12250, included in a group of pure copper. The study was conducted to determine the causes and mechanisms of failure in elbow cooler. To find out more about the causes of the failure of this material then, an analysis of the failure of the observations in the form of macro, micro observations (metallographi), testing of SEM-EDAX, XRD testing, as well as simulating fluent. Based on the results of testing that was done failures in the cooler tube elbow caused by corrosion-erosion and cavitation. The mechanism of erosion-corrosion due to the combination of high flow rates and corrosive fluids. At high flow rates physically corrosive fluids clicking eliminate erosion and corrosion protection layer thus opening reactive metal underneath. Suspended slurries strengthen and accelerate corrosion-erosion (Accelerate corrosion-erosion attack).Key Word : Cooler, coorosion-erosion, elbow tube cooler.